SiO2/TiO2 composite powders deposited on cement-based materials: Rhodamine B removal and the bonding mechanism. (30th April 2020) - Wang, Dan; Hou, Pengkun; Stephan, Dietmar; Huang, Shifeng; Zhang, Lina; Yang, Ping; Cheng, Xin
Highlights: Preparation and application two SiO2 @TiO2 core-shell composites with different deposited densities. Excellent rhodamine B-removal efficiency before and after curing and accelerated weathering processes. Pozzolanic reaction of samples and calcium hydroxide and changed morphologies. Changing the structure of the C-S-H. Promoting the transformation of C3 S. Abstract: For surface functionalization of cement-based materials with photocatalytic properties, weak adhesion between photocatalysis and matrix worsens these properties and results in poor weathering resistance in outdoor environments. To overcome these problems, in this study, two SiO2 /TiO2 composites, with different deposited densities of TiO2 nanoparticles on a SiO2 sphere, were prepared and used for surface coating of cement-based materials. The two composites show different efficiencies. The photocatalytic results show that the coated cement pastes exhibited excellent rhodamine B-removal efficiency before and after curing and accelerated weathering processes, indicating that SiO2 in the system has a crucial effect as a 'glue' preventing the release of TiO2 . The bonding mechanism was revealed by the reaction of the samples and main components and hydration products (such as CH, C-S-H and C3 S).